Role of Some Natural products as a Disinfectant on Color of GC-SoftLiner - Rabee Al-Sumaidae, Rana (Tikrit Journal of Pharmaceutical Sciences, 2023)
The study aims to evaluate the effect of some natural products (nigella sativa. sesame, flax amd ginger oil) (Emad factory/mosul/Iraq) in relation to nystutin suspension on color of GC-Soft Liner Fifly Sample were prepared frum-GC-extra soft lining material, they were (10*10%2mm). Half of the samples for each group were immersed for 8hr in these oils after they had been infected with Candida albicans and incubated [ur 48hr, the other half of the samples immersed for Bhr daily fur one month. This study compared antifungal efficiency before and after immersion in distilled water (Negative Control), nystatin suspension (100000 LU/ml as a positive control), nigella sativa, sesame, flax and ginger oil. Color of samples tested by Vita — Easy Shade system, the statistical tests used were analysis of variance, Durinet T-test. The resulls demonstrated that there were significant differences between all tested oils znd DW in refution to antifungal action, and no significant differences between all tested oils and D.W iu relation 0 color of GC-solt Lining maternal al (P=0.05). All the tested natural oils were effective antifungal agents and would be accepted and safe in relation to the color of soft hnet.